Expanding application of digital pathology in Japan - from education, telepathology to autodiagnosis - Tsuchihashi Yasunari (BMC, 2011)
Abstract Background Digital pathology, i.e., applications of digital information technologies to pathology practice, has been expanding in the recent decades and the mode of pathology diagnostic practice is changing with enhanced precision. In the present study the changing processes of digital pathology in Japan were investigated and trends to future were discussed. Methods The changing status of digital pathology was investigated through reviewing the records of annual meetings of the Japanese Research Society of Telepathology and Pathology Informatics (JRST-PI) and of the Japanese pathology related medical and informatics journals. The results of the Japanese questionnaire survey conducted in 2008-2009 on telepathology and virtual slide were also reviewed. In addition effectiveness of an experimental automatic pathology diagnostic aid system using computer artificial intelligence was investigated by checking its rate of correct diagnosis for given prostate carcinoma digital images. Results Telepathology played a central role in the development of digital pathology in Japan. Both macroscopic and microscopic pathology digital images were routinely generated and used for diagnostic purposes in major hospitals. Virtual slide (VS) digital images were used first for education then for conference, consultation and also gradually for routine diagnosis and telepathology. The experimental automatic diagnostic aid system achieved the rate of correct diagnosis around 95% for prostate carcinoma and its use for automatic mapping of cancerous areas in a given tissue image was successful. Conclusions Advance in the digital information technologies gave revolutionary impacts on pathology education, conference, consultation, diagnosis, telepathology and also on pathology diagnostic procedures in Japan. The future will be bright for pathologists by the advanced digital pathology but we should pay attention to make the technologies and their effects under our control.